Does Postoperative Cognitive Decline Result in New Disability After Surgery?. Issue 6 (December 2021) - Deiner, Stacie; Liu, Xiaoyu; Lin, Hung-Mo; Jacoby, Rachelle; Kim, Jong; Baxter, Mark G.; Sieber, Frederick; Boockvar, Kenneth; Sano, Mary
Abstract : Objective: Establish whether POCD is associated with new disability after surgery, which would inform whether POCD impacts patient-centered outcomes. Background: POCD is a decline in neuropsychiatric tests scores from presurgical baseline which occurs in approximately 15% of older patients 3 months after surgery. POCD is a research construct meant to investigate patient and family reports of older adults who were "never the same after surgery." However, many patients with POCD do not perceive difficulty with thinking and memory, and the question remains whether POCD impacts patient function. Methods: We performed a prospective cohort study of 167 older adults undergoing major noncardiac surgery (requiring at least a 2-day hospital stay). Exclusion criteria were: history of dementia, cardiac or intracranial procedure, inability to consent for themselves, or emergency surgery. We administered formal neuropsychiatric testing (Alzheimer Disease Research Center UDS battery), basic and instrumental activities of daily living (Alzheimer Disease Research Center IADLs), pain (geriatric pain measure), and depression screening (hospital depression and anxiety scale) before and 3 months after surgery. We recorded all patient refined diagnostic related groups codes, blood pressure, anesthetics and narcotics administered, surgical and anesthesia duration, and measured complications and severity, length of stay, and readmissions. Results: Patients with POCD (21/167, 14.1%) had twice the proportion of new impairment in IADL as compared to those without POCD (57% vs 27%, P = .01). The most common areas of decline were social activities, ability to find items around the house, remember appointments, shop and pay for items, do laundry, drive a car/use public transport, and do housework. Predictors of IADL change after surgery included POCD, presurgical cognition, presurgical function, postoperative depression, and the development of postoperative complications. Conclusions: Patients with POCD experience a much higher incidence of new disability after surgery. Baseline cognitive or functional limitations are also risk factors for new disability. Many patients are not aware of their limitations before surgery. Future study is needed to identify practical ways to routinely screen patients and reduce risk. Patients need to be informed of their risk for new disability after surgery to inform their medical decision making. Abstract : Supplemental Digital Content is available in the text